Eksposisi Keluaran 3:14 Mengenal Allah Dan Implikasinya Bagi Orang Percaya - Lispan; Januario; Andreta (Shema: Jurnal Teologi Injili dan Pendidikan Kristen, 2022)
Knowing God knowing and believing in the existence of God, the statement of the name "Yahweh"/Jehovah to Moses as the liberator of the Israelites as God's self-revelation. The name of Allah is translated “I AM THAT I AM” which denotes all personal, adequate aspects of the essence of God's character. Reveal His nature and person, presence, and also His divine will and purpose. According to expert David Noel, the word "ehyeh" is vocalized as a form of the verb Qal, which is a form influenced by the tradition that is used as a standard by the Septuagint or perhaps an older tradition. This research includes biblical texts, so the approach that will be used is a hermeneutic approach in the form of exegesis studies, aiming to gain a better understanding of the context under study. In Exodus 3:14 there is the word "ehyeh asher ehye" translated "I cause what exists, what exists". People who know God will do God's will, great and great deeds for His glory, do God's commandments, "we know God, if we keep His commandments." (1John 2: 3 Abstrak Bahasa Indonesia Mengenal Allah mengetahui dan meyakini adanya Allah, pernyataan nama “Yahweh”/Yehova kepada Musa sebagai pembebas bangsa Israel sebagai penyataan diri Allah. Nama Allah diterjemahkan “AKU ADALAH AKU” yang menunjukkan semua aspek pribadi, memadai dari hakikat dari karakter Allah. Menyatakan sifat dan pribadi, kehadiran, dan juga kehendak serta tujuan ilahi-Nya. Menurut para ahli David Noel kata “ehyeh” divokalisasikan sebagai bentuk kata kerja Qal, merupakan bentuk mendapat pengaruh dari tradisi yang dijadikan patokan oleh Septuaginta atau mungkin tradisi yang lebih tua. Penelitian ini mencakup teks Alkitab, maka ancangan yang akan digunakan adalah ancangan hermeneutik dengan bentuk kajian eksegesis, bertujuan untuk memperoleh pemahaman yang lebih baik mengenai konteks yang diteliti. Dalam Keluaran 3:14 terdapat kata “ehyeh asher ehye” diterjemahkan “ Aku yang menyebabkan ada, apa yang ada”. Orang mengenal Allah akan melakukan kehendak Allah, perbuatan hebat dan besar bagi kemuliaan-Nya, melakukan perintah Allah, “kita mengenal Allah, yaitu jikalau kita menuruti perintah-Nya.” (1Yoh. 2: 3-6).